Evaluation of the Results and Complications of Transabdominal Preperitoneal Laparoscopic Inguinal Hernia Repair in Patients with a History of Radical Prostatectomy - Izadpanahi, Mohammad Hossein; Milasi, Rana (Urology Journal, 2020)
Purpose: Radical prostatectomy is one of the most common urological surgeries. Inguinal hernia is a well-known complication of radical prostatectomy. There are many controversies about selection of surgical techniques for repair of inguinal hernia. Traditionally laparoscopic approach was contraindicated for patients with history of lower abdominal surgery, but recent studies showed that it could be safe and successful and even has some advantages over open repair. In this prospective study we evaluated outcomes of laparoscopic hernia repair in patients who previously underwent radical prostatectomy. Materials and Methods: In this prospective study, 34 consecutive patients diagnosed with inguinal hernia after radical retropubic prostatectomy underwent laparoscopic transabdominal inguinal repair and followed up for outcomes and complications. Results: The surgery duration was 167.44 ± 52.85 min (75-230 min). No intraoperative complications occurred. Patients were discharged within 20.79 ± 4.76 hours (12-34 hours). 69.8% of cases (30 patients) needed analgesic administration. No conversion to open surgery occurred. There were 9.3% (4 hernias) hernia recurrences. We followed patients for 9.9 ± 5.33 months (2-19 months). Conclusion: It is concluded that TAPP for inguinal hernia repair after radical prostatectomy has good results and is effective. But according to rate of recurrence, its safeness is conflicting. We notice no major complication in our patients during the time of follow up. This may be due to safety of the operation in the proposed patients.